Mathematical Communication Ability Reviewed from Student’s Self-Esteem on MiC Learning Process with Nuance of Jepara Culture - Riawati, Beti; Karomah Dwidayati, Nur; Rosyida, Isnaini (Unnes Journal of Mathematics Education Research, 2020)
Mathematical communication ability is a term for solving problems, and self-esteem is a factor that determine student’s success to get achievements. A good mathematical communication ability and self-esteem can help students to solve a problem. The aim of this research are (1) to know the quality of MiC learning process with nuance of Jepara culture to improve student’s mathematical communication ability, and (2) to know the student’s mathematical communication ability reviewed from self-esteem on MiC learning process with nuance of Jepara culture. The type of this research is mixed methods model concurrent embedded. The population of this research is the students of grade X MIA Pecangaan Senior High School, Jepara. The subject of this research determined based on the low and high self-esteem category. Data collection technique are questionnaire, observation, test, and interview. The result of this research showed that (1) MiC learning process with nuance of Jepara culture has a high quality both qualitative and quantitative, (2) mathematical communication ability on students with low self-esteem can describe mathematic ideas in visual form well. Beside, mathematical communication ability on students with high self-esteem can describe mathematic ideas in visual form well, can state the daily events to language or mathematic symbols, can understand and evaluate the mathematic ideas on solving problems in writing, and they also can communicate the conclusion of an answer problem suitable with the question.